The effects of Hyperloop on the long-range personal and freight transportation industry in Europe - Alves, Filipe Coelho (2020)
The transportation industry has experience little disruptive technologies since the introduction of airplane, over 100 years ago. Nevertheless, the sector is of extreme importance in connecting people and businesses together. Hyperloop technology brings the promise of a new, faster and cleaner mode of transport that could disrupt current transportation modes. To understand the potential effects of the disruptive technology, the author analyses the current long-range freight and personal transportation industry, the modes and its characteristics and the competition between them. Hyperloop has more potential to affect the personal segment, and particularly airlines. On the freight side, the impact will be confined to the road and air modes of transport, and its degree will be lower. Once the technology is fully operational, airlines should focus on intercontinental routes where air transportation is the only mode available. LCC, relying solely on continental routes, will have difficulties in making the transition and many will leave the market. FSA and LCC will engage in M&A for operational efficiency and enlargement of hub-and-spoke networks. Air freight carriers rely mostly in intercontinental routes and should not experience a business model change. Road transportation is increasingly focusing on the “last-mile” of transportation services and may benefit from decongestion of roads caused by a shift to Hyperloop in the long-range freight transportation in Europe. Environmental impact of mode shift is considerable and is mostly caused by a shift in domestic and continental routes from air to Hyperloop transportation.